The Impact of Intellectual Capital, Business Risk, and Institutional Ownership on Firm Value - Alwaini, Khadafi; Tarmidi, Deden (LifeSciFi, 2024)
This study aims to analyze the effect of board diversity on the relationship between intellectual capital, business risk, and institutional ownership with firm value. With the unit of analysis of companies operating in the Property, Real Estate, and Construction Building sectors listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Using purposive sampling, a final sample of 184 firms was obtained. Multiple regression analysis was used to test the hypothesis. The result indicate that intellectual capital and business risk have a positive impact on firm value, while institutional ownership has a negative impact. Additionally, the study finds that intellectual capital and institutional ownership, as represented by both male-dominated and female-dominated of the Board of Directors (BoD), do not significantly affect firm value. However, a male-dominated BoD has a more significant impact compared to a female-dominated BoD, while both have a positive effect on business risk in the company.